Fibrin Clot Formation under Oxidative Stress Conditions - Kaufmanova, Jirina; Stikarova, Jana; Hlavackova, Alzbeta; Chrastinova, Leona; Maly, Martin; Suttnar, Jiri; Dyr, Jan Evangelista (Antioxidants, 2021)
During coagulation, the soluble fibrinogen is converted into insoluble fibrin. Fibrinogen is a multifunctional plasma protein, which is essential for hemostasis. Various oxidative posttranslational modifications influence fibrinogen structure as well as interactions between various partners in the coagulation process. The aim was to examine the effects of oxidative stress conditions on fibrin clot formation in arterial atherothrombotic disorders. We studied the changes in in vitro fibrin network formation in three groups of patients-with acute coronary syndrome (ACS), with significant carotid artery stenosis (SCAS), and with acute ischemic stroke (AIS), as well as a control group. The level of oxidative stress marker malondialdehyde measured by LC-MS/MS was higher in SCAS and AIS patients compared with controls. Turbidic methods revealed a higher final optical density and a prolonged lysis time in the clots of these patients. Electron microscopy was used to visualize changes in the in vitro-formed fibrin network. Fibers from patients with AIS were significantly thicker in comparison with control and ACS fibers. The number of fibrin fibers in patients with AIS was significantly lower in comparison with ACS and control groups. Thus, oxidative stress-mediated changes in fibrin clot formation, structure and dissolution may affect the effectiveness of thrombolytic therapy.